The Validity and Practicality of the Dunia Geometri Application as an Interactive Mathematics Learning Medium for Students - Muhammad Zazid Solakhudin; Nabila Nur Tasnima; Naufalia Adani; Choirul Anwar; Enika Wulandari; Wulan Izzatul Himmah (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
This study aims to develop and evaluate the validity and practicality of a mathematics learning application called Dunia Geometri as an interactive learning medium for junior high school students. The research background is rooted in students’ low understanding and motivation in learning three-dimensional geometry, which is further exacerbated by the limited availability of innovative and interactive learning media. To address this issue, the Dunia Geometri application was designed to integrate 3D visualizations, instructional videos, and tiered evaluation features that support student engagement and conceptual understanding. The research employed a Research and Development (R&D) approach using the ADDIE model, limited to the stages of Analysis, Design, and Development. Data were collected using validation sheets completed by media and material experts, as well as practicality questionnaires administered to teachers and students. The results of expert validation indicated a high validity score (87.69%), categorized as very valid. Similarly, the practicality test showed high ratings from teachers (85.71%) and students (79.33%), demonstrating that the application is easy to use and effectively supports classroom learning activities. The implementation of interactive technology in the Dunia Geometri application has been shown to enhance students’ motivation and understanding of geometric concepts. These findings confirm that the application exhibits a high level of validity and practicality, making it an effective learning medium for teaching geometry at the junior high school level. Future development is recommended to incorporate gamification and augmented reality features to further enhance engagement and improve long-term learning outcomes.